Lexicographie artistique formes, usages et enjeux dans l'Europe moderne/ Artistic lexicography : forms, uses and issues in Early Modern Europe - Trouvé, Stéphanie; Heck, Michèle-Caroline; Freyssinet, Marianne (Théorie des Art, 2018)
ven if they are contradictory, the different senses give thickness and subtlety to the concept.            The journey of a notion in time and space then also contributes to broadening our understanding of a cultural history between universality and identity within the artistic diversity that characterizes modern Europe.